1983
DOI: 10.1103/physrevlett.51.885
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Branching Ratio for the Dissociative Recombination ofH3++e

Abstract: The dissociative recombination of H 3 + with electrons can have two exit channels, namely e + H 3 + -H + H + H (channel I), and e + H 3 + -H 2 + H (channel II). A new technique has been developed which has been used to determine the relative contributions of channels I and II to the overall recombination process. Over the energy range from 0.01 to 0.05 eV it has been found that channel I dominates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(14 citation statements)
references
References 23 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…Mitchell et al 11 found that the thermalized H 3 þ ion is converted into 3 H or H 2 þ H at the moment of impact due to dissociative recombination. 11,26,33 In this way, the H 3 þ ion brings not only energy to break the Si-Si bond (2.3 eV) but also atomic H to passivate the Si dangling bonds and to form a stable desorption product.…”
Section: The Effect Of An Externally Applied Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitchell et al 11 found that the thermalized H 3 þ ion is converted into 3 H or H 2 þ H at the moment of impact due to dissociative recombination. 11,26,33 In this way, the H 3 þ ion brings not only energy to break the Si-Si bond (2.3 eV) but also atomic H to passivate the Si dangling bonds and to form a stable desorption product.…”
Section: The Effect Of An Externally Applied Biasmentioning
confidence: 99%
“…The H 3 þ ion converts into either molecular and atomic hydrogen (H 2 þ H) or only atomic hydrogen (3 H) by dissociative recombination at the moment of impact. 11 Desorbing species are also formed near the ion penetration depth and this shows the chemical activity of the hydrogenic ions. 10 Atomic H diffusing through Si can break a weak Si-Si bond, it can passivate the Si dangling bonds formed, and it can recombine with another H atom and form molecular H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Geppert & Larsson 2008). To elucidate these completely by experimental methods is also far from trivial and it was as late as in the 1990s when Datz et al (1995) ingeniously applied the technique of merged ion electron beams using a storage ring in conjunction with a previously invented grid technique (Mitchell et al 1982) to obtain solid information about these distributions. Subsequently, heavy-ion storage rings like ASTRID (Denmark), TSR (Heidelberg) and CRYRING (Stockholm, Sweden) have been successfully used as tools for investigations of astrophysically relevant DR reactions (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A second point to made about the Gougousi et al three-body mechanism is that it requires the formation of long-lived H 3 * Rydberg molecules in DR of H 3 + . Such have been only been found in merged-beam [43] but not in ISR experiments.…”
Section: Afterglow Data After 1984mentioning
confidence: 83%